Improving students’ generative AI literacy: A single workshop can improve confidence and understanding (Journal of Applied Learning and Teaching, 2024)
With the emergence of generative artificial intelligence (genAI), it has become increasingly important to ensure that students are equipped with AI literacy to use these tools effectively and appropriately. We ran a 90-minute, optional workshop for students to demonstrate how to use genAI in the assessment process appropriately. By the end of the workshop, participants felt significantly more confident in using genAI, had more intentions to use genAI, and understood the University’s genAI policy better. The types of genAI use that participants envisioned shifted from general academic and life uses to specific, acceptable uses for learning. Students could identify some methods for assessing the output of genAI. However, it is suggested that this skill needs more development.